2020
DOI: 10.1051/0004-6361/202038749
|View full text |Cite
|
Sign up to set email alerts
|

Interstellar oxygen along the line of sight of Cygnus X-2

Abstract: Interstellar dust permeates our Galaxy and plays an important role in many physical processes in the diffuse and dense regions of the interstellar medium (ISM). High-resolution X-ray spectroscopy, coupled with modelling based on laboratory dust measurements, provides a unique probe for investigating the interstellar dust properties along our line of sight towards Galactic X-ray sources. Here, we focus on the oxygen content of the ISM through its absorption features in the X-ray spectra. To model the dust featu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 87 publications
1
11
0
Order By: Relevance
“…Residuals in this energy range were present in multiple previous RGS studies of the O K edge (e.g., Costantini et al 2012;Pinto et al 2013). They were later discussed in particular by Psaradaki et al (2020), who interpret them as instrumental features in RGS (see Figure 6 of their paper). Regardless of the origin of the features, we decided to ignore the 22.25-24 Å band in this study.…”
Section: Appendix a The Gain Shift Of The Epic Pn Timing Mode Spectramentioning
confidence: 68%
“…Residuals in this energy range were present in multiple previous RGS studies of the O K edge (e.g., Costantini et al 2012;Pinto et al 2013). They were later discussed in particular by Psaradaki et al (2020), who interpret them as instrumental features in RGS (see Figure 6 of their paper). Regardless of the origin of the features, we decided to ignore the 22.25-24 Å band in this study.…”
Section: Appendix a The Gain Shift Of The Epic Pn Timing Mode Spectramentioning
confidence: 68%
“…The interference pattern created by the photoelectron waves during the absorption of an X-ray photon in dust grains can in fact give rise to X-ray absorption fine structures (XAFSs). These features are expected to be commonly associated with Mg, Si, andO (e.g., Zeegers et al 2017, 2019;Costantini et al 2019;Rogantini et al 2019Rogantini et al , 2020Psaradaki et al 2020) and have been identified in the X-ray spectra of X-ray-bright Galactic sources thanks to high-resolution XMM-Newton and Chandra observations (e.g., Lee et al 2002;Ueda et al 2005;Kaastra et al 2009;Lee 2010;Pinto et al 2010Pinto et al , 2013Costantini et al 2012;Valencic & Smith 2013;Psaradaki et al 2023). The presence of dust in the ISM could lead to significant biases when measuring the column density in the direction of X-ray sources with models that do not consider dust absorption and scattering (Corrales et al 2016;Smith et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The interference pattern created by the photoelectron waves during the absorption of a X-ray photon in dust grains can in fact give rise to X-ray absorption fine structures (XAFS). These features are expected to be commonly associated to Mg, Si and O (e.g., Costantini et al 2019;Rogantini et al , 2020Psaradaki et al 2020;Zeegers et al 2017Zeegers et al , 2019, and have been identified in the X-ray spectra of X-ray bright Galactic sources thanks to high-resolution XMM-Newton and Chandra observations (e.g., Lee et al 2002;Lee 2010;Ueda et al 2005;Kaastra et al 2009;Pinto et al 2010Pinto et al , 2013Costantini et al 2012;Valencic & Smith 2013;Psaradaki et al 2022). The presence of dust in the ISM could lead to significant biases when measuring the column density in the direction of X-ray sources with models that do not consider dust absorption and scattering (Corrales et al 2016;Smith et al 2016).…”
Section: Introductionmentioning
confidence: 99%